Aromatase as a target for treating endometriosis. Issue 9 (25th July 2018) - Mori, Taisuke; Ito, Fumitake; Koshiba, Akemi; Kataoka, Hisashi; Tanaka, Yukiko; Okimura, Hiroyuki; Khan, Khaleque N.; Kitawaki, Jo
Abstract: Endometriosis is a common gynecological disease that causes various clinical symptoms, such as chronic pelvic pain, dysmenorrhea and infertility, seriously affecting women's health and their quality of life. The symptoms and endometriotic lesions are relieved, in many cases, after menopause, when estrogen levels are lowered. Therefore, endometriosis is considered to be estrogen‐dependent. Aromatase, the enzyme responsible for the last step of estrogen biosynthesis converting testosterone and androgen to estrogen, was previously reported to be more abundant in endometriotic tissues than in the normal endometrium, leading to an increased local estrogen concentration. Therefore, aromatase is considered a key therapeutic target for regulating local estrogen biosynthesis in endometriosis. A more complete understanding of the mechanisms that modulate aromatase and its activity is required to develop novel estrogen‐targeted therapies for endometriosis. In this review article, we outline the current understanding of the pathological processes involved in estrogen production in endometriosis and propose novel strategies to treat this disorder.